Propriétés antioxydantes et anti-inflammatoires des polyphénols de la rue fétide Ruta graveolens - BELAID, Ahlam; BELLIL, Hafida Nawel (My University, 2017)
The aim of the current work was to quantify the total flavonoid and polyphenol content of Ruta graveolens, and the evaluation of the antioxidant and anti-inflammatory activities of its polyphenols. According to the results, his plant is rich in polyphenols and flavonoids (4,163 ±0,0394 mgEAG/gE and 1,397 ±0,033 mgEQ/gE respectively). For the antioxidant activity, two tests were used, DPPH and b-carotene. Polyphenols of Ruta possess a good activity with values of 5,61±0,139 mg EAA/g E and 1,99±0,21 mg EAA/g E). After that, the anti-inflammatory activity of this plant polyphenols was explored by two tests: Inhibition of albumin denaturation and human red blood cell membrane stabilization method. Ruta graveolens polyphenols had inhibited the denaturation of albumin (0,118±0,138 mg EI/g E) and also were able to stabilize the membrane of human red blood cell (4,629±0,101 mg ED/g E).
Keywords: Ruta graveolens; polyphenols; antioxidant activity; anti-inflammatory activity; Ruta graveolens; polyphénols; activité antioxydante; activité anti-inflammatoire.